Crystal structure of trans-tetraaquabis(4-(pyridin-4-ylsulfonyl)pyridine-κN)cobalt(II) diperchlorate dihydrate, C20H28Cl2CoN4O18S2 - Zhou Rong; Jie Liu An; Zhang Fan (Zeitschrift für Kristallographie - New Crystal Structures, 2016)
C20H28Cl2CoN4O18S2, monoclinic, P21/c (no. 14), a = 8.0756(2) Å, b = 17.4328(4) Å, c = 11.5696(2) Å, β = 106.477(1)°, V = 1561.88(6) Å3, Z = 2, Rgt(F) = 0.0456, wRref(F2) = 0.1298, T = 296 K.